2017
DOI: 10.1097/ogx.0000000000000517
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Use in Pregnancy, Neonatal Abstinence Syndrome, and Childhood Outcomes: Executive Summary of a Joint Workshop by the Eunice Kennedy Shriver National Institute of Child Health and Human Development, American College of Obstetricians and Gynecologists, American Academy of Pediatrics, Society for Maternal-Fetal Medicine, Centers for Disease Control and Prevention, and the March of Dimes Foundation

Abstract: (Abstracted from Obstet Gynecol 2017;130(1):10–28) This article provides a summary of the “Opioid Use in Pregnancy, Neonatal Abstinence Syndrome, and Childhood Outcomes” workshop convened by the Eunice Kennedy Shriver National Institute of Child Health and Human Development on April 4 and 5, 2016, and cosponsored by the American College of Obstetricians and Gynecologists (ACOG), the American Academy of Pediatrics, the Society for Maternal-Fetal Medicine, the Centers for Disease Control and Prevention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
90
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(94 citation statements)
references
References 0 publications
4
90
0
Order By: Relevance
“…4e6 The standard treatment approach to opioid use disorders in pregnancy includes initiation of medically assisted therapy (MAT) with long-acting opioids, traditionally methadone but more recently buprenorphine. 6,7 Compared with untreated opioid use disorder, medically assisted therapy has been associated with improved utilization of prenatal care, higher newborn birthweights, decreased risk of HIV infection, and lower rates of recidivism when compared with detoxification or medication-free treatment. 6,8 However, the use of MAT in pregnancy results in a risk of NOWS, which ranges from 47% to 57%.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…4e6 The standard treatment approach to opioid use disorders in pregnancy includes initiation of medically assisted therapy (MAT) with long-acting opioids, traditionally methadone but more recently buprenorphine. 6,7 Compared with untreated opioid use disorder, medically assisted therapy has been associated with improved utilization of prenatal care, higher newborn birthweights, decreased risk of HIV infection, and lower rates of recidivism when compared with detoxification or medication-free treatment. 6,8 However, the use of MAT in pregnancy results in a risk of NOWS, which ranges from 47% to 57%.…”
mentioning
confidence: 99%
“…6,7 Compared with untreated opioid use disorder, medically assisted therapy has been associated with improved utilization of prenatal care, higher newborn birthweights, decreased risk of HIV infection, and lower rates of recidivism when compared with detoxification or medication-free treatment. 6,8 However, the use of MAT in pregnancy results in a risk of NOWS, which ranges from 47% to 57%. 6 A factor that may have an impact on the incidence and severity of NOWS is the dose of long-acting opioid therapy during pregnancy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On top of the limitations of current scoring systems, disease severity in NOWS is known to be heterogenous and can be affected by a variety of clinical factors (e.g., types of utero opioid exposure, concomitant exposure to other substances, and gestational age) as well as genetic factors. 114,115 For these reasons, we could foresee limitations of using PD modeling based on withdrawal scores to guide dosing frequency in the weaning phase. On the other hand, there have been an increasing number of clinical studies aiming to simplify weaning protocols empirically.…”
Section: Current Dosing and Pharmacometrics-driven Dosing Optimization In Nowsmentioning
confidence: 99%
“…The Centers for Disease Control and Prevention reported that the prevalence of OUD more than quadrupled in the United States from 1999 to 2014 (from 1.5/1000 deliveries to 6.5/1000) [1]. The mainstay of medical management is to place these patients on medications for opioid use disorder (MOUD) that use longer-acting opioid drugs such as methadone or buprenorphine [2][3][4][5][6]. These two medications are administered in daily oral/sublingual dosages.…”
Section: Introductionmentioning
confidence: 99%